Infancy As A Defence: Constitutionality Of The Legal Protection Provided To The Child Offenders (Journal of Namibian Studies : History Politics Culture, 2023)
It has long been believed that children lack the mental maturity and development to discriminate between right and bad behavior, and that they are incapable of judging their own behavior. They are unable to comprehend the repercussions of their acts. For instance, if a child hits someone with a stone while playing, they are unable to consider the possibility that this could cause them serious harm, possibly even death. It is practically hard to develop and align the child's mens rea and actus reus, therefore in such instances, we are unable to prosecute and punish the child under the appropriate offenses. This is mostly because it is difficult to establish the mens rea and the subsequent actus reus. Children should also be treated like children, not like adults, as they have not yet reached the mental, physical, or biological maturity necessary to comprehend the repercussions of their actions. “Therefore, through ages since the criminal laws have evolved, it has become a common notion that a child who lacked the capacity to understand the wrongfulness of his conduct could not be held criminally culpable”[1].